Starting Mandibular Advancement Device Therapy in Patients with Good Protrusive Capacity: A Randomized Pilot Study - Marie Marklund (Galenos Yayinevi, 2023)
Objective:Discomfort has been related to the poor acceptance of a mandibular advancement device (MAD) in patients with obstructive sleep apnea. The present study compared severe initial side effects between a smaller and a larger degree of mandibular advancement in patients with a good protrusive capacity.Methods:Consecutive patients with obstructive sleep apnea and a good protrusive capacity (≥8 mm) were randomized to start treatment with the mandible advanced by either 70% of maximum protrusion (Adv70%) or by 4 mm (Adv4mm) in a pilot study with a parallel design. The main outcome was tenderness or pain in the teeth or jaws using a 0-10 visual analogue scale (VAS) (from "not at all" to "very extensive") or excluded use because of side effects during the first week of treatment. Secondary outcomes included salivation problems and bite changes.Results:Eighteen patients were randomly selected and 17 patients fulfilled the study protocol. Four patients in the Adv70% group and none in the Adv4mm group reported severe tenderness or pain (VAS ≥7) on five or more of the seven days (p=0.03). The degree of mandibular advancement measured in millimeters correlated with the number of days with severe side effects, r=0.64 (p=0.006). The secondary side effects were minor.Conclusion:Starting MAD treatment with 70% mandibular advancement was related to more severe side effects during the first week of treatment compared with a smaller fixed millimeter value in patients with a good protrusive capacity in this pilot study.